ФИЗИКАГА ОИД МАСАЛАЛАРНИ ЕЧИШДА МОДЕЛЛАШТИРИШ МЕТОДИ ВА ЭКСПЕРИМЕНТАЛ МАСАЛАЛАРНИ ТАҲЛИЛ ҚИЛИШНИНГ ЎЗИГА ХОС ЖИҲАТЛАРИ - Эштемиров, А.Н. (SCIENCE and SOCIETY, 2022)
The article explains that for university students in solving complex problems of the physics course, along with mathematical modeling, it is possible to achieve the desired and high results through the methods of solving experimental problems.
Keywords: experimental; cognitive; experiment; ECC; physics